Pancreatic stem cells originate during the pancreatic progenitor developmental stage - Jacques, Krystal; Coles, Brenda L. K.; van der Kooy, Derek (Frontiers in Cell and Developmental Biology, 2025)
Previously isolated adult pancreatic precursors called pancreatic multipotent progenitors (which make both pancreatic endocrine and exocrine cell types) originate from the Pancreatic Duodenal Homeobox 1 (PDX1) pancreatic developmental lineage. The embryonic time point at which adult pancreatic multipotent progenitor cells emerge has not been established. We have employed the use of two models: a human embryonic stem cell (hESC) to beta-cell cytokine-induced differentiation protocol and a mouse lineage tracing model during early development to isolate clonal pancreatic spheres. The results show that insulin-positive clonal spheres can be isolated as early as the pancreatic endoderm stage as well as the pancreatic progenitor stage during the hESC to beta-cell lineage differentiation model and that they can be isolated only as early as the pancreatic progenitor stage during mouse embryogenesis. Further, pancreatic clonal sphere-forming cells isolated from the pancreatic progenitor stage in embryonic mice display multipotentiality, and those isolated at a later gestational age demonstrate self-renewal ability. These findings suggest that pancreatic precursors isolated from mouse embryonic time points have stem cell properties and that the pancreatic progenitor stage in hESC development may be the optimal time to capture and expand these stem cells and make large numbers of beta cells.